Alveolar arch shapes and its relation to complete denture retention - Theresia Tarigan; Ismet Danial Nasution (Dentistry Faculty, 2020)
The alveolar ridge consists of denture bearing mucosa, sub-mucosa and periosteum, and residual alveolar bone. After tooth extraction, the remaining alveolar bone undergoes a remodeling process that leads to morphological reduction and alteration, which results in the change in alveolar ridge forms. However, it does not change alveolar arch shapes. This literature review aimed to analyze the relationship of alveolar arch shapes with complete denture retention. According to House (1958), alveolar arch shapes classified into three classes: Class I-square, Class II-tapering, Class III-ovoid. Those three alveolar arch shapes have a difference in the denture bearing area, with the largest denture bearing site on Class I-Square alveolar arch shape. Some factors that influence complete denture retention are adhesion, cohesion, interfacial force, oral and facial musculature, atmospheric pressure, undercut, rotational insertion path, parallel walls, and gravity. The alveolar arch shapes can affect retention regarding the size of the denture bearing area.The alveolar arch forms with a wider denture bearing area provide more considerable surface contact between the denture and mucous membranes. The forces resulting from those factors of retention might produce more excellent complete denture retention. The square arch shape is the alveolar arch shape with the largest denture bearing area. Hence, the square arch shape is believed to have the best complete denture retention.KEYWORDS: arch shape; retention; complete denture; denture bearing area